COVID-19, social isolation and the mental health of autistic people and their families: A qualitative study. (May 2022) - Pellicano, Elizabeth; Brett, Simon; den Houting, Jacquiline; Heyworth, Melanie; Magiati, Iliana; Steward, Robyn; Urbanowicz, Anna; Stears, Marc
The COVID-19 pandemic and its policy responses have had a detrimental effect on millions of people's mental health. Here, we investigate its impact on autistic people and their families using qualitative methods. Specifically, we addressed: how did autistic people experience an increase in social isolation during the initial lockdown? And how was their mental health impacted by lockdown? Autistic and non-autistic researchers conducted 144 semi-structured interviews with autistic adults (n = 44), parents of autistic children (n = 84) including autistic parents and autistic young people (n = 16). We deployed thematic analysis to identify key themes. The enhanced social isolation accompanying the pandemic had a serious and damaging impact on autistic people's mental health and subjective wellbeing. They spoke of intensely missing friends and more incidental forms of social connection. They also reported intense dissatisfaction with the substitution of embodied, person-to-person connection in health services by online/telephone-based alternatives, sometimes accompanied by serious negative consequences. These findings reveal the fundamental importance of supporting autistic people to maintain direct and incidental social contact during the pandemic and beyond. They speak against established theories that downplay autistic people's need for human connection and the extent to which they have been affected by social isolation during lockdowns. Lay abstract: In this study, we show that autistic people and their families have found it very difficult to deal with the lockdowns during the COVID-19 pandemic. Autistic and non-autistic researchers spoke to 144 people, including 44 autistic adults, 84 parents of autistic children and 16 autistic young people (12–18 years old). We asked them about their everyday lives and mental health during lockdown. People told us that they enjoyed having fewer obligations and demands compared to pre-COVID-19 life. They felt that life was quieter and calmer. But people also told us again and again how much they missed meeting people in real life, especially their friends, and their therapists and support workers. People told us that their mental health suffered because they did not have contact with their friends and services. Importantly, many people (including researchers) think that autistic people do not want friends or to be around people. But our results show that is not true. Many autistic people do want friends and to be around other people. Some people's mental health has been damaged by not being able to see people during COVID-19. Autistic people need support in many areas of life so they can keep socialising and seeing their friends even through difficult times, like pandemics.